Intellectual goals of the leaders of alash and their national knowledge (Herald of Journalism, 2022)
In the early twentieth century, during the national liberation struggle of the Kazakh people, the Alash movement emerged. His main goal was the creation of an independent Kazakh state. The “Alash” people were highly educated people, true scholars, who had deep knowledge in social, humanitarian and natural science knowledge. The article deals with the figures of “Alash” and representatives of the Kazakh administrative elite, scientific and creative intelligentsia laid the foundation of the Kazakh state- hood. By the author of this article, it was defined that works of Kazakh journalism and Alash intellectuals still require a lot of research to determine that.Key words: newspaper,article,the chiefeditor, author,state, Alashintelligentsia.